Relationship between morphology and trophic ecology in an assemblage of passerine birds in riparian forests of the Paraná River (Argentina) - Quiroga, Virginia Mariela (2018)
We describe the ecomorphology of an assemblage of bird species found in riparian forests of the Middle Paraná River, Argentina. We sought to determine (1) the more important morphological characteristics that separate coexisting species, (2) whether such separation was related to the trophic ecology of each species and (3) whether a priori guilds showed morphological similarity. We tested the hypotheses that (a) a species' morphology is related to the trophic ecology of that species and (b) that species of a priori guilds are morphometrically more similar to each other than to species of different a priori guilds. For this, we considered an assemblage of 29 species of birds from riparian forest that were sampled with mist nets during the 2011 and 2014 breeding seasons. We obtained morphometric measurements of captured individuals and supplemented those data with measurements from museum specimens. Trophic characterisation (diet and trophic microhabitat) was based on a literature review. Results showed a separation of bird species as a function of variables related to trophic ecology (diets and trophic microhabitats) and morphology. After controlling for phylogenetic constraint, species' morphology partially reflected the trophic ecology of the species, supporting the central hypothesis of the ecomorphological discipline and showing that the use of trophic and morphometric data provides complementary data to improve the guild organisation of riparian bird assemblages.